Biodegradation of synthetic estrogen using bioelectrochemical system and degradation pathway analysis through Quadrupole-time-of-flight-mass spectrometry. (April 2022) - Syed, Zainab; Sogani, Monika; Kumar, Anu; Rajvanshi, Jayana; Sharma, Gopesh; Sonu, Kumar
Graphical abstract: Highlights: 78% EE2 degradation in bioelectrochemical system using EE2 adapted cells. Enhanced EE2 removal and increased power output in BES with EE2 as a co-substrate. Detection of significant intermediate metabolites during EE2 degradation in BES. Proposed hypothetical pathway for EE2 degradation by R. palustris strain MDOC01. Improved surface characteristics due to Plasma peroxide treatment of anode material. Abstract: Synthetic estrogenic compounds such as 17α-ethinylestradiol (EE2) are significant environmental contaminants. This research studied the biodegradation of EE2 utilizing the EE2 adapted cells isolated from a dairy farm waste site in suspension flask vis-a-vis Bioelectrochemical System (BES) and compared the power output in the BES with and without EE2 as a co-substrate. 78% removal of EE2 was observed in the BES as against 60% removal in suspension flasks. The maximum power density in the BES increased about 53% when EE2 is used as a co-substrate. The EE2 biodegradation studied using HPLC and Q-TOF methods, also proposes a hypothetical pathway for EE2 degradation by the newly isolated strain Rhodopseudomonas palustris MDOC01 and reports the significant metabolites like nicotinic acid and oxoproline being detected during bioelectrochemical treatment process of EE2. Study also suggests that Plasma peroxide treatment of anode material enhanced the overall performance in terms of biodegradation efficiency and power output.